2020
DOI: 10.3390/nano10112097
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Mechanical Properties of 3Y-TZP Nanofiber Mats

Abstract: The mats of yttria-stabilized tetragonal zirconia nanofibers were prepared using electrospinning. The effect of calcination temperature in the range of 600–1200 °C on their microstructure, phase composition and mechanical properties was investigated. Phase composition of the nanofibers did not change in all ranges of the calcination temperatures, while the average grain size increased from 8 to 39 nm. Nanoindentation testing of the mats showed a decrease in the hysteresis loop energy in samples with higher cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Thus, our results are in agreement with different studies that reported that zirconia nanofibers or ZrO 2 composites may have pro-osteogenic properties, have good mechanical biocompatibility, and improve the metabolism of bone precursor cells. Furthermore, they could also be considered as a self-regulation material that possesses an excellent osteoinductive capacity that could modify the deposition of ECM by bone cells during differentiation or in response to the surface material, because the osteoblast cell functions could be substrate-sensitive, either with respect to stiffness, roughness, or to the size of the composition of the material [16,17,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our results are in agreement with different studies that reported that zirconia nanofibers or ZrO 2 composites may have pro-osteogenic properties, have good mechanical biocompatibility, and improve the metabolism of bone precursor cells. Furthermore, they could also be considered as a self-regulation material that possesses an excellent osteoinductive capacity that could modify the deposition of ECM by bone cells during differentiation or in response to the surface material, because the osteoblast cell functions could be substrate-sensitive, either with respect to stiffness, roughness, or to the size of the composition of the material [16,17,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the synthesis of polymeric nano-or microfibers with bioceramics via electrospinning has been widely applied in bone tissue engineering; due to its large surface/volume ratio, the process allows modification of their physical or chemical properties and enables precise control over the shapes and structures of the fibers, which is often reported in the literature [8,[15][16][17][18][19]. Likewise, another versatile, low-cost, safe (does not employ high voltage), scalable, and versatile method that produces micro/nanoscale fibers from different synthetic and natural polymers is the air-jet spinning (AJS) method.…”
Section: Introductionmentioning
confidence: 99%